1999
DOI: 10.1136/jcp.52.3.203
|View full text |Cite
|
Sign up to set email alerts
|

The possible role of hypoxia in the formation of axonal bulbs.

Abstract: Aims-To assess the possible role of hypoxia in the formation of axonal bulbs. Methods-Study material comprised sections from 28 brains showing evidence of cerebral hypoxia with no history of head injury, four with a history of head trauma but no evidence of hypoxic change, eight with a history of head trauma and hypoxic change, and four from control brains originally described as "diVuse axonal injury." These were subjected to microwave antigen retrieval and immunohistochemistry using monoclonal antibodies to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 20 publications
(19 reference statements)
1
33
1
Order By: Relevance
“…Harrington et al [2] demonstrated that 11 of 20 cases with histological changes of hypoxia without head injury showed positive APP staining and survival times from 1 h to 3 months. Kaur et al [14] reported that 12 of 25 cases of hypoxia without head injury showed positive APP staining and survival times from a few hours to 68 days. However, specific staining patterns of the labeled axons were not mentioned in their investigations [2,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Harrington et al [2] demonstrated that 11 of 20 cases with histological changes of hypoxia without head injury showed positive APP staining and survival times from 1 h to 3 months. Kaur et al [14] reported that 12 of 25 cases of hypoxia without head injury showed positive APP staining and survival times from a few hours to 68 days. However, specific staining patterns of the labeled axons were not mentioned in their investigations [2,14].…”
Section: Discussionmentioning
confidence: 99%
“…These axonal bulbs form usually in the presence of both intracranial and systemic pathology, such as cerebral infarction/ hemorrhage, meningitis, bronchopneumonia, hypoglycemia, and drug intoxication as well as in cases of ventilator support [5,7,[12][13][14][15]. In particular, hypoxia and ischemic brain damage without head injury show the formation of axonal bulbs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings further emphasize the inter-and intrapatient variability that has been previously detailed in other clinicopathological studies of fatal malaria. [2][3][4][5] Recent literature has raised the possibility that hypoxia, 26 raised intracranial pressure, 26 -29 and hypoglycemia 30 can cause AI. We found no association between AI and intracranial pressure or hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 It remains unclear whether TAI in white matter is entirely the result of primary injury or if commonly occurring secondary insults (such as increased intracranial pressure (ICP), hypoxia, or hypotension) after TBI can influence the extent and severity of axonal injury. [12][13][14][15] Reduction and avoidance of elevations in ICP continue to be the mainstays of treatment patients with for severe TBI. 10,11 Although there is evidence that sustained elevations in ICP > 20 mm Hg after severe TBI are associated with poor outcome, efficacy of threshold-targeted interventions has not been thoroughly established.…”
Section: Introductionmentioning
confidence: 99%